Interdiffusion in narrow InGaAsN∕GaAs quantum wells - Liu, W. (2013)
Interdiffusion in In0.32Ga0.68As0.984N0.016 /GaAs multiple quantum wells with well widths of 2 and 4 nm, respectively, was investigated both experimentally and theoretically. Maximum blueshifts of 206 and 264 meV in the photoluminescence spectra were observed. Secondary ion mass spectrometry showed that both In–Ga and N–As interdiffusions played key roles for the large blueshifts. The significant In–Ga interdiffusion occurred at 650 °C while the N diffusion occurred at a temperature above 700 °C. The theoretical results are in good agreement with the experimental observations.